2014
DOI: 10.1108/jsocm-04-2013-0025
|View full text |Cite
|
Sign up to set email alerts
|

In the mood for [the right kind of] social marketing communication

Abstract: Purpose – The effectiveness of social marketing communication should depend both on message features and on the psychological characteristics of message recipients. This premise was tested in an experiment focused on why consumers may respond differently to different types of pro-recycling advertisements. The message feature was the way in which the advertisements were framed. The psychological characteristic of the message recipient was the respondent's mood. The paper aims to discuss these is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…In contrast, in a different study reviewed, negative-framed messages were more effective at promoting mammography use among low-income women (Randolph & Viswanath, 2004; Schneider et al, 2001). Using humor to evoke a positive mood likely augmented the impact of the gain-based message strategy (Anghelcev & Sar, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a different study reviewed, negative-framed messages were more effective at promoting mammography use among low-income women (Randolph & Viswanath, 2004; Schneider et al, 2001). Using humor to evoke a positive mood likely augmented the impact of the gain-based message strategy (Anghelcev & Sar, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Communicating solutions and efficacy information within a gain frame rather than within a loss frame raised hopeassociated with more supportive attitudes (Nabi et al, 2018). Still, findings from other environmental communication studies ranged from no difference between the two frames when combined with emotion-priming (Perrin, 2011) or used in combination with guilt/shame emotional frames (Baek & Yoon, 2017) to their effects being variable and dependent on other factors such as people's moods (Anghelcev & Sar, 2014) or mind-sets (White, MacDonnell, & Dahl, 2011).…”
Section: Outcome Framesmentioning
confidence: 99%
“…For example, a processed product like pizza can be advertised in a virtue frame by highlighting the nutritional value of its ingredients (e.g., calcium content, whole grains) or their natural origin (e.g., natural cheese); the very same processed product could be advertised in a vice frame by emphasizing words like indulge, savory, taste and by highlighting the enjoyment of the sensory experience brought about by its flavors. Research has shown that such variations in framing promotional messages can lead to significant differences in perception, even when the advertisements look very similar and only slight changes are implemented (e.g., Anghelcev & Sar, 2014).…”
Section: Perceived Healthfulness Of Vice Versus Virtue Foods: From DImentioning
confidence: 99%
“…In this exploratory article, we examine how slight variations in advertising messages influence consumers' perceptions of the healthfulness of processed organic food products, in the context of an online experiment using a national sample of US organic shoppers (N = 375). Drawing from marketing and communication research on message framing (Anghelcev & Sar, 2014;Entman, 1993), consumer psychology studies on schema congruity (Cheong & Kim, 2011;Meyers-Levy & Tybout, 1989;Stayman, Alden, & Smith, 1992) and food studies research on vice and virtue products (van Doorn & Verhoef, 2011;Wertenbroch, 1998), we propose an interaction effect between the way the promotional message is framed (vice vs. virtue) and the type of advertised processed product (organic vs. conventional) on perceptions of healthfulness. Two other hypotheses are also advanced.…”
Section: Introductionmentioning
confidence: 99%